Penggunaan tanah bawah tanah bagi maksud pembangunan di Kuala Lumpur - Arrifin, Arfaliza (2013)
The rapid growth of urban development has resulted in the use of underground land as an alternative choice to maximize the use of space in the middle of the city. In addition, the use of underground land has contributed to the sustainable development and improvement of the environment and quality of life. Therefore, this study will focus on the aspects of the implementation and development of the projects involved using underground land. This study will examine the current use of underground land and its potential for future development in Malaysia. The issues discusses in this study will includes the types of underground land development in Malaysia and the implementation of the regulations and legislation for underground land development. To achieve the objectives, the technique of interview will be used in order to produce a qualitative analysis that will describe the views and information of the respondents, where its conclusion will supports to achieve each objective. Finally, recommendations are put forward to address the weaknesses identified in particular problems related to provisions of the laws on underground land development